The role of the polycomb complex in silencing alpha-globin gene expression in nonerythroid cells. - Garrick, D; De Gobbi, M; Samara, V; Rugless, M; Holland, M; Ayyub, H; Lower, K; Sloane-Stanley, J; Gray, N; Koch, C; Dunham, I; Higgs, D (2008)
Although much is known about globin gene activation in erythroid cells, relatively little is known about how these genes are silenced in nonerythroid tissues. Here we show that the human alpha- and beta-globin genes are silenced by fundamentally different mechanisms. The alpha-genes, which are surrounded by widely expressed genes in a gene dense region of the genome, are silenced very early in development via recruitment of the Polycomb (PcG) complex. By contrast, the beta-globin genes, which lie in a relatively gene-poor chromosomal region, are not bound by this complex in nonerythroid cells. The PcG complex seems to be recruited to the alpha-cluster by sequences within the CpG islands associated with their promoters; the beta-globin promoters do not lie within such islands. Chromatin associated with the alpha-globin cluster is modified by histone methylation (H3K27me3), and silencing in vivo is mediated by the localized activity of histone deacetylases (HDACs). The repressive (PcG/HDAC) machinery is removed as hematopoietic progenitors differentiate to form erythroid cells. The alpha- and beta-globin genes thus illustrate important, contrasting mechanisms by which cell-specific hematopoietic genes (and tissue-specific genes in general) may be silenced.